The nation's gaps offsetting budgeting - Dayao, Fernando S., Jr.; Esguerra, Emmanuel F. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
This paper introduces a new normative public budgeting theory named “Nation’s Gaps Offsetting Budgeting (NGOB)”, a theory designed to solve Vladimir Orlando Key’s basic budgeting problem - “Faced with limited resources, on what basis shall it be decided to allocate X dollars to Activity A, instead of Activity B?” NGOB, as its name implies, prescribes that the primary basis of budgetary decisions and prioritizations should be the offsetting of the more pressing nation’s gaps of the particular country/place. As preliminary background, this paper narrates the history and development of public budgeting from antiquities up to the current years. Then, this paper evaluates the existing normative public budgeting in order to answer why it is necessary to come up with a new alternative public budgeting theory. The basic concepts, rationale, principles, and the processes adopted are discussed therein to provide for a detailed introduction of NGOB, in theory and proposed practice. Application of NGOB in actual practice necessitates designing a new approach in presenting the budget, which is introduced in this paper as “Macro-Micro Budget Approach.” NGOB likewise requires formulation of a nation’s performance and results monitoring framework introduced herein as “Nation’s Overall Performance Index” (NOPI). The research problem in this paper is whether or not NGOB can provide sufficient and definitive answer to aforesaid Key’s budgeting problem. To test and illustrate the applicability of NGOB into actual budget preparation and in solving the Key budgeting problem, an Alternative Fiscal Year (FY) 2018 NGOB-based Budget of the Philippine National Government was prepared, consistent with the principles and parameters of NGOB. The result of NGOB application showed that it has inherent theoretical and application limitations, and there are instances that it could not be applicable in giving a definitive answer to Key’s budgeting question. It is therefore concluded that while NGOB can be regarded as a new alternative rational theory in public budgeting, it is not an all-encompassing theory that can solve the Key budgeting problem sufficiently.
Thesis (Master in Development Economics) -- University of the Philippines Diliman
Keywords: Finance, Public -- Philippines; Budget process -- Philippines